Aleutian Ancorinidae (Porifera, Astrophorida): Description of three new species from the genera Stelletta and Ancorina - Lehnert, Helmut; Stone, Robert P. (Zootaxa, 2014)
Two new species of the genus Stelletta and one new species of Ancorina are described from the Aleutian Islands of Alaska and compared to congeners of the region. This is the first record of the genus Ancorina in the North Pacific Ocean. Stelletta ovalae Tanita 1965 is also reported for the first time from the Bering Sea and Alaska.